Splanchnic Aneurysms & Possible Etiology - J. Demos, Nicholas; McGovern, Patrick; Smith, Peter; Demos, Victoria (Journal of Digestive Disorders And Diagnosis, 2019)
Four cases are reported with splanchnic aneurysms of the branches of the main arteries. Three of the cases presented as emergencies. Possible rupture was present in Case 2 and true rupture in Case 4. The etiology of Cases 1 and 2 may have been a floxacin antibiotics, Table 1. This report is the first clinical chronological association of the antibiotics and arterial and aortic pathology. This association was supported by nationwide research by Pasternak, 11. Detailed experimental work done on mice showed connective tissue fragmentation and arterial cell injury. Apparently, the above antibiotic induced mitochondrial DNA damage and dysfunction, 9.
Keywords: splanchnic; mesenteric; aneurysms; Flocaxin; gastrointestinal